A Method for Analyzing Mortality Data Collected in Follow-up Studies - Woolson, R. F.; Tsuang, M. T.; Fleming, J. A. (Methods of Information in Medicine, 1978)
An approach to the analysis of mortality data gathered in long-term follow-up studies is described. The methodology is appropriate for situations in which it is of interest to contrast a study sample to a larger reference population. The main advantage of the approach is the ability to handle the age heterogeneity of the study group. Two variations of the general method are developed: the unconditional and conditional methods. The conditional approach is illustrated by application to data which arose in a study in psychiatric epidemiology.
Keywords: Survival Analysis; Standardization of Rates; Mortality Studies